Aromatic and aliphatic production of catalytic pyrolysis of lignin using ZSM-5/Al-SBA-15 catalyst derived from high-calcium fly ash. (November 2021) - Vichaphund, Supawan; Wimuktiwan, Panida; Soongprasit, Chakrit; Sricharoenchaikul, Viboon; Atong, Duangduen
Abstract: In this work, lignin was utilized as biomass feedstocks to study the feasibility of fuels and chemical production, while fly ash was used for synthesizing ZSM-5 (FA-ZSM-5) and SBA-15 (FA-SBA-15) catalysts for upgrading pyrolysis products. The use of fly ash offers several benefits such as reducing the fly ash disposal cost, solving environmental problems, and significantly increasing high valued products. Catalytic fast pyrolysis of kraft lignin using ZSM-5/ SBA-15 catalyst prepared from fly ash was studied using a pyrolysis-GC/MS system. The influence of temperature (400–600°C) during thermal pyrolysis, the FA-ZSM-5 and FA-SBA-15 ratios (1:0, 2:1, 1:1, 1:2, 0:1), and lignin-to-catalyst ratios (1:5 and 1:10) on the hydrocarbon selectivity was investigated. Non-catalytic pyrolysis volatiles consisted of a high proportion of guaiacol compounds (G-type, 66.7%) and p-hydroxyl phenols (H-type, 18.0%). The presence of zeolite catalysts contributed to enhance both aliphatic and aromatic production, while a proportion of guaiacyl decreased significantly. The highest selectivity of aliphatic and aromatic HCs was achieved at feed to catalyst ratios of 1:10. Coupling HZSM-5 and Al-SBA-15 catalysts were more reactive in converting the alkoxy-phenol (G-type) and p-hydroxyphenyl compounds (P-type) toward both aliphatic HCs and monocyclic-aromatic HCs (MAHs), particularly benzene, toluene and xylene (BTX). Among all catalysts, FA-ZSM-5/ FA-SBA-15 ratio of 1:2 showed the optimum dual catalyst ratio to enhance the highest yield of aliphatic and aromatic hydrocarbons of 15.1 and 21.4 % with the acceptable yield of phenolic compounds (34%). ZSM-5/ SBA-15 catalyst prepared from fly ash showed high efficiency to convert solid lignin to MAHs (BTX). The decrease in the PAHs selectivity seemed to be good performing of this dual catalyst because it expected to decrease the coke formation on the catalyst surface.